2018
DOI: 10.1016/j.solmat.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CdCl2 passivation treatment on microstructure and performance of CdSeTe/CdTe thin-film photovoltaic devices

Abstract: The effects of the CdCl 2 passivation treatment on thin-film CdTe photovoltaic films and devices have been extensively studied. Recently, with an addition of CdSeTe layer at the front of the absorber layer, device conversion efficiencies in excess of 19% have been demonstrated. The effects of the CdCl 2 passivation treatment for devices using CdSeTe has not been studied previously. This is the first reported study of the effect of the treatment on the microstructure of the CdSeTe /CdTe absorber. The device eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 13 publications
(21 reference statements)
8
30
0
Order By: Relevance
“…We find a strong correlation between selenium concentration, high material luminescence efficiency, sub-gap transitions at 1.36 eV, and longer diffusion lengths, all at the sub- around the front contact of the device. The setup accurately measures the J-V parameters and the agreement of these measurements with an externally certified photovoltaic device has been shown in previous work [18].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We find a strong correlation between selenium concentration, high material luminescence efficiency, sub-gap transitions at 1.36 eV, and longer diffusion lengths, all at the sub- around the front contact of the device. The setup accurately measures the J-V parameters and the agreement of these measurements with an externally certified photovoltaic device has been shown in previous work [18].…”
Section: Discussionsupporting
confidence: 59%
“…This is similar to the as-deposited device. However, in contrast to the as-deposited device, which has a sharp interface between the CdSeTe and CdTe layers (see [18], and Supplementary Figure 1), the CdCl 2 -treated cell shows a gradual decrease in the selenium concentration with distance away from the front interface. This means that selenium signal is detected towards the back of the cell, in the CdTe layer (for clarity now referred to as the 'interdiffused CdTe' region).…”
Section: Selenium Diffusion Into the Cdte Layermentioning
confidence: 93%
“…Use of a chloride compound was chosen due to the well‐known chlorine‐related benefits of recrystallization, grain growth, and p‐type doping (bicomplexes with native defects) in CdTe. There is evidence that similar processes have been already applied in some laboratories but without a study of the process' effect …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that similar processes have been already applied in some laboratories but without a study of the process' effect. [24][25][26][27][28] Beach et al suggested that the defects induced by CdCl 2 , probably Cl-induced donor, increased the solubility of the Cu at Cd substitutional sites impurities Cu − Cd , which are considered acceptors. 29 The CuCl 2 is applied after the standard CdCl 2 activation treatment because combining activation treatment and copper doping in a single step is not possible: CdCl 2 activation treatment is applied at a temperature which would cause a very large Cu diffusion.…”
mentioning
confidence: 99%
“…The CdCl2 treatment is especially important with CST devices, as it causes the diffusion of the graded layer. This will also affect texture change [11].…”
Section: Discussionmentioning
confidence: 99%